Serial Mediation Roles of Alexithymia and Loneliness in the Association Between Family Function and Internet Addiction Among Chinese College Students - Zhao, Ying; Zhang, Kuo; Griffiths, Mark D. (Frontiers in Psychology, 2022)
A lot of previous research has highlighted the negative consequences of internet addiction. However, relatively few is known about the underlying mechanism for internet addiction among college students in relation to family function. The present study explored the relationship between family function and internet addiction among college students, as well as the mediating effects of alexithymia and loneliness. A sample of 783 Chinese college students were administered a number of psychometric scales including the ‘General Function’ subscale of the Chinese version of the Family Assessment Device, Toronto Alexithymia Scale, UCLA Loneliness Scale, and Revised Chinese Internet Addiction Scale. The results showed that family function was negatively associated with internet addiction; the association was significantly mediated by alexithymia; the association was significantly mediated by loneliness; and alexithymia and loneliness sequentially mediated the association. The total mediating effect was 66.57%. The results of the present study are of great significance to the prevention and intervention of internet addiction among college students.